Effectiveness of a measure program to prevent admission hypothermia in very low-birth weight preterm infants - Jamil Pedro de Siqueira Caldas; Fernanda de Castro Millen; Juliana Fernandes de Camargo; Paula Almeida Cavalcanti Castro; Ana Letícia da Fonseca Camilo; Sérgio Tadeu Martins Marba (Elsevier, 2018)
Objective: To evaluate the effectiveness of a thermoregulation bundle for preventing admission hypothermia in very low-birth weight preterm infants. Methods: Interventional study with retrospective evaluation of data undertaken in a tertiary neonatal unit including all very low-birth weight preterm infants (<1500 g) born at and admitted to the unit. Two periods were compared: before intervention (PI; 01/01/2012 to 02/28/2014_ and after intervention (PII; 04/01/2014 to 11/30/2016). The intervention started in March 2014. At PI procedures in the delivery room were: placement in a crib with a radiant heat source, doors always closed, polyethylene body plastic bag, double cap (plastic and cotton mesh), room temperature between 24 to 27 °C and transport to neonatal unit in a pre-heated incubator (36-37.0 °C). At PII, there was a reinforcement on not opening the plastic bag during the entire resuscitation process, even at an advanced stage, and the anthropometric measures and routine care were performed in the neonatal unit. Maternal, delivery, and neonatal variables were compared. Admission hypothermia was considered when admission axillary temperature was <36.0 °C. Periodic results were shown to the team every six months and results were discussed. Results: The incidence of admission hypothermia was reduced significantly in PII (37.2 vs. 14.2%, p < 0.0001) and admission temperature medians were higher (36.1 vs. 36.5 °C, p < 0.001). At PII, there was an increase in the number of infants transported with oxygen (49.5 vs. 75.5%, p < 0.0001). No differences were observed regarding birth weight and gestational age. Conclusion: There was a very important reduction in admission hypothermia incidence and a higher median admission temperature after continued protocol implementation. Resumo: Objetivo: Avaliar a efetividade de um programa de medidas para prevenção de hipotermia à admissão em recém-nascidos pré-termo de muito baixo peso. Métodos: Estudo de intervenção com coleta retrospectiva de dados em unidade neonatal terciária que incluiu todos os recém-nascidos pré-termo de muito baixo peso (< 1.500 g) nascidos e admitidos na unidade. Foram comparados dois períodos: antes da intervenção PI - 01/01/2012 a 28/02/2014 e depois da intervenção PII - 01/04/2014 a 30/11/2016. O mês de março de 2014 foi o início da intervenção. Em PI as medidas em sala de parto foram: recepção em berço de calor radiante, portas sempre fechadas, uso de saco plástico corporal, colocação de dupla touca (plástico e malha) na cabeça, temperatura ambiental entre 24-27 °C e transporte em incubadora aquecida (36-37,0 °C). No PII reforçou-se a não abertura do saco plástico durante toda reanimação mesmo que avançada e dados antropométricos e cuidados rotineiros realizados na unidade de internação. Variáveis maternas, de parto e neonatais foram comparadas entre os dois períodos. A hipotermia à admissão foi considerada quando temperatura axilar < 36,0 °C. Resultados parciais foram apresentados e discutidos com a equipe semestralmente. Resultados: A incidência da hipotermia à admissão diminuiu significativamente em PII (37,2 x14,2%, p < 0,0001) e a mediana de temperatura foi mais elevada (36,1x36,5° C, p < 0,001). Houve aumento significativo do número de crianças transportadas com oxigênio em PII (49,5 x 75,5%, p < 0,0001). Não houve diferenças para peso ao nascer e idade gestacional. Conclusão: Houve redução acentuada de hipotermia à admissão e melhora na mediana da temperatura de admissão hospitalar em recém-nascidos pré-termo de muito baixo peso após implantação do protocolo. Keywords: Hypothermia, Very low birth weight infant, Quality of health care, Palavras-chave: Hipotermia, Recém-nascido de muito baixo peso, Qualidade da assistência à saúde